Translating Evidence-Based Practices to Usable Interventions for Young Children With Autism. (June 2018) - Johnson, LeAnne D.; Fleury, Veronica; Ford, Andrea; Rudolph, Brenna; Young, Kelsey
Increased numbers of young children identified with autism combine with changing paradigms for service delivery models to create a need to ensure that information is available to facilitate implementation of effective practices in children's natural learning environments. A recent synthesis that identifies evidence-based practices (EBPs) for children with autism is used as the basis for exploring the degree to which existing literature provides information that meaningfully supports the translation of those practices to usable interventions within the routine services provided by educators. Our review of 113 studies focusing on 13 EBPs for children with autism below the age of 6 revealed inconsistent and incomplete reporting within and across practices. Based on this review, we offer a discussion on how the reporting practices of researchers may facilitate or hinder the generation of usable knowledge needed by implementation science when guiding large-scale adoption and use of interventions.